Metabolic bone disease of prematurity – an overview. Issue 1 (January 2017) - Nallagonda, Srinivas; Nallagonda, Madhavi; Deorukhkar, Anjum
Abstract: With improved survival of extreme preterm and very low birth weight infants, there has been an increased incidence of metabolic bone disease (MBD). The last couple of decades have seen better awareness of the condition which in turn has led to improvement in the management and prevention of MBD. MBD occurs because there is difficulty in matching intrauterine mineral accretion rate after birth. The lack of a single specific and sensitive diagnostic test frustrates early diagnosis in many babies. Investigations like dual energy X-ray absorptiometry (DEXA) and quantitative ultrasound scanning are helpful in establishing a diagnosis but currently used mostly in research studies. A pragmatic approach for paediatricians is to pre-empt the formal diagnosis and supplement those at risk with adequate minerals and vitamin D, whilst monitoring the blood markers of MBD. Despite the noticeable short-term complications and stunting effect on childhood height, the prognosis of MBD is generally good. The aim of this article is to provide the reader with an improved understanding of the aetiopathogenesis, and offer some practical guidance on when and how to investigate and manage the metabolic bone disease of prematurity.